“VENEXIT” – VENICE SECESSION MOVEMENT - Savanović, Aleksandar (Politeia, 2018)
The research analyses the Veneto’s secessionist movement. Focus of the research is on 2014 plebiscit. As a wider theoretical framework for research we will use the theory of the social contract as the mainstream approach in contemporary political philosophy, with huge relevance for our understanding of the political community. According to this theoretical model, secession is legally possible only-and-only-if there is a consent or consensus from all sides within political community. Usually (in political practice), this means that there is some kind of agreement between secessionists and the central government. Other sorts of arguments (economic, cultural, and historical) cannot provide a sufficient justification for secession. Mandatory reason for secession is the consent of others. Other reasons are not sufficient, but these reasons are non-mandatory also. Secession is possible by the consent of others, even without any other reason except request of secessionists to leave their present state. Discussion about Veneto case from 2014 was a typical example of this theoretical approach. Requests from the cultural, economical and historical facts were correct (often and in many cases), and has been possible to defend these arguments in correct scholarly debate and analysis. Nevertheless, absence of consent of the government in Rome, prevents any legal consequences for changing the status of Veneto.